2022
DOI: 10.1017/9781108609364
|View full text |Cite
|
Sign up to set email alerts
|

Insect Diapause

Abstract: Our highly seasonal world restricts insect activity to brief portions of the year. This feature necessitates a sophisticated interpretation of seasonal changes and enactment of mechanisms for bringing development to a halt and then reinitiating it when the inimical season is past. The dormant state of diapause serves to bridge the unfavourable seasons, and its timing provides a powerful mechanism for synchronizing insect development. This book explores how seasonal signals are monitored and used by insects to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 1,628 publications
5
91
6
1
Order By: Relevance
“…However, whether and how DH31 CA neurons are regulated in response to dormancy-inducing conditions has not been elucidated. Previous studies have reported that the circadian clock system is involved in the regulation of reproductive dormancy in many insect species (4, 53, 72, 73), including D. melanogaster (27, 51, 60, 74). Therefore, we propose that, to an extent, circadian clock neurons, such as 5 th s-LNv, s-LNv, LNd, and DN1p are connected with DH31 CA neurons and modulated its activity under dormancy-inducing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, whether and how DH31 CA neurons are regulated in response to dormancy-inducing conditions has not been elucidated. Previous studies have reported that the circadian clock system is involved in the regulation of reproductive dormancy in many insect species (4, 53, 72, 73), including D. melanogaster (27, 51, 60, 74). Therefore, we propose that, to an extent, circadian clock neurons, such as 5 th s-LNv, s-LNv, LNd, and DN1p are connected with DH31 CA neurons and modulated its activity under dormancy-inducing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…During such unfavorable conditions, organisms often suspend or retard their normal development, growth, and physiological functions, known as dormancy (1). Dormancy has been intensively studied in insects as its control could benefit many aspects of industry and agriculture (2)(3)(4). Previous studies have revealed that a fraction of insects enter dormancy at the adult stage under dormancy-inducing conditions leading to multiple metabolic and behavioral changes, including slowed or halted reproductive maturation known as reproductive dormancy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations